Sexual and Gender-Based Violence and Vulnerability to HIV Infection in Uganda: Evidence from Multilevel Modelling of Population-Level HIV/AIDS Data - Patrick Igulot (Social Sciences, 2022)
Background: Sexual and gender-based violence (SGBV) is highly prevalent in Uganda and its link with HIV infection and compromising access to HIV/AIDS services is known. However, current evidence is controversial. Most of the studies indicate a positive relationship but a few indicate otherwise. Moreover, there is no research examining the effects of community-level SGBV on HIV infection. Objectives: This research explores the association between SGBV and vulnerability to HIV infection. Methods: Multilevel binary logistic regression is applied to secondary data of Uganda AIDS Indicators Survey conducted in 2011. The survey data comprises 12,153 women and 9588 men. Results: SGBV significantly increases the likelihood of HIV infection, with victims having 34%, 1.34 [1.06–1.70] higher odds than non-victims. At the community level, wealth, and pre-sex alcohol abuse are important determinants. Conclusions: Vulnerability to the risk of HIV infection in Uganda is associated with individual-level and community factors. Effective HIV prevention policies need to pay attention to victims of SGBV using individual- and community-level strategies.